CMOS image sensor with NMOS-only global shutter and enhanced responsivity. - Wany, M.
Most CMOS image sensors today use the rolling shutter approach to control the integration time. This pixel architecture is advantageous where minimal pixel size is required to increase resolution or reduce over all chip size. For imaging of a fast moving object or when used with pulsed illumination, the rolling shutter approach is not suitable since it leads to severe distortion. Therefore, these applications require image sensors with a global shutter pixel architecture, which incorporates a sample-and-hold element in each pixel. Due to the optical exposure of the in-pixel storage element, shutter leakage is critical. First approaches which use separate wells in the pixel to isolate the storage node from the photodiode showed good shutter efficiency, but are bulky and led to large pixels with poor fill factor and bad responsivity. This paper presents an NMOS-only pixel with a global shutter and subthreshold operation of the NMOS sample-and-hold transistor to increase optical responsivity by a factor of five to 9 υV/photon, including fill factor.
Keywords: CMOS image sensors; NMOS S/H transistor; NMOS-only global shutter; NMOS-only pixel; Fast moving object imaging; Global shutter pixel architecture; High-responsivity imaging; Industrial vision; Pulsed illumination; Responsivity enhancement; Sample/hold element; Shutter leakage; Subthreshold operation